Critical analysis of factors determining sustainable development of territories in a strategic perspective - E. A. Kirillova; N. A. Danilenko (Вестник университета)
The main interpretations of terms, development trends, foreign and domestic experience within the concept of sustainable development of territories have been considered. The importance of cooperative interaction and cooperation between actors in the same area in the context of existing constraints, barriers and opportunities for the deployment of the processes under consideration, has been confirmed. A statistical comparative analysis of the dynamics of changing trends in the interaction between research organisations and industrial enterprises of the regions has been carried out in comparison with Russian and global trends. The interrelationships between the key factors relating to financial support processes, infrastructure capacity and the research and education component have been revealed and their impact on territorial development has been highlighted. Scientific research methods such as analysis and generalization and correlation analysis were used within the framework of the article.